Industrial training report: Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) / Nazurah Hishamuddin - Hishamuddin, Nazurah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This report describes the experiences gained during a six-month internship at Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) from 5 August 2024 to 17 January 2025. As a Library Management student at Universiti Teknologi Mara (UiTM), completing an internship is a requirement in the 7th semester. This practical experience helps assist between what I’ve learned in class and how libraries function. This report is divided into four chapters. Chapter 1 introduces the background of PERPUSTAM. Chapter 2 explains how different departments work together within PERPUSTAM. Chapter 3 details my tasks during the internship, such as organizing library activities, managing digital resources, and even cataloguing materials. Finally, Chapter 4 reflects on my overall experience, including how I applied theoretical knowledge in a real library setting and the valuable lessons I learned.